Hubungan pengetahuan lingkungan dan sikap konservasi terhadap perilaku lingkungan santri di Pondok Pesantren Darut Tafsir - Hasanah, Fauziyah; Syartinilia, Syartinilia; Amin, Akhmad Arif (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2022)
Islamic boarding schools are Islamic institutions that can make an important contribution to environmental care. Islamic boarding schools are an essential element and can form agents of change in people's behavior and attitudes towards the environment. This study aims to examine the level of students' knowledge, the attitudes and the behavior of students at Darut Tafsir Islamic Boarding School towards the environment. and to analyze the relationship among the three. This research was conducted at Darut Tafsir Islamic Boarding School, Ciampea, Bogor from February to April 2022. This study used multiple regression analysis to analyze the relationship between students' knowledge and conservation attitudes and students' environmental behavior. Descriptive analysis is used to see the level of environmental knowledge, conservation attitudes and environmental behavior of students. The results of the study showed that the average level of environmental knowledge among students was 73.5%, and the attitude towards conservation was 60.5%. Students' environmental behavior averaged 65.3%. The coefficient of determination R2 in the regression is 0.639, meaning that the contribution of environmental knowledge and conservation attitudes to environmental behavior is only 63.9%. To improve students' environmental behavior, it is necessary to improve environmental education in the boarding schools.